AN EXPERIENCE OF BRONCHOTOMY AND RESECTIONAL PROCEDURES AFTER FAILED BRONCHOSCOPIC FOERIGN BODY RETRIEVAL - Khan, Yasser Saeed; Majeed, Farhan Ahmed; Shah, Syed Zahid Ali; Abbasi, Munir Ahmad; Raza, Ahmed; Imtiaz, Tashfeen; Imran, Mohammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Foreign body bronchus is a surgical emergency and is associated with a high mortality if neglected or complicated. The objective of this study was to analyse the outcome of bronchotomy and resectional procedures after failed bronchoscopic foreign body retrieval. Methods: This study of 24 cases of bronchotomy and resectional procedures after failed bronchoscopic foreign body retrieval was done from June 2008 to June 2009 and March 2010 to Sep 2013. Patients after failed retrieval of foreign body by bronchoscopy either by ENT specialists or thoracic surgeons underwent bronchotomy or resectional procedures were included in the study. We used the posterolateral thoracotomy approach for the surgical procedures. Results: Bronchotomy and resectional procedures were done in 24 cases. Age of patients ranged from 2 years to 51 years. Most patients were children and right side was mostly involved. Bronchotomy procedures were 10 (41%) and resectional surgeries were 13 (58%). Emergency lobectomies were 3 out of 13 resectional surgeries. Right intermedius bronchus was opened up and incision was extended in the direction of foreign body in 6 cases and left bronchus intermedius was opened in 4 cases. Haemoptysis was the main symptom in late presenters. Range of objects retrieved in our study was from pins, needles to whistles. Conclusion: Retention causes endobronchial obstruction with stasis leading to irreversible damaged parenchyma. Foreign body with structural changes require resection, others can be offered bronchotomy which is a safe procedure for retained non retrievable foreign bodies. Keywords: Outcome, resectional procedures, early and delayed presentation